OPTIMASI KARAKTERISTIK SENSORI PROPORSI TEPUNG KOMPOSIT DARI SERAT PANGAN LARUT DAN GELATIN TERHADAP MUTU BAKSO IKAN KERAPU - Anggela Anggela (Agroindustrial Technology Journal, 2023)
Kerapu is a potential fishery commodity in East Kalimantan, but the development of diversification of its derivative products needs to be developed more widely. Meatballs are generally made using the basic ingredients in the form of meat, but the high-fat content can trigger degenerative diseases such as high blood pressure, coronary heart disease, and stroke. Therefore, Kerapu is known to be high in unsaturated fatty acids (omega-3) which is very good for health, so Kerapu is used in making fishballs of this research. The combination of the interaction formulation of soluble dietary fiber (porang glucomannan or seaweed flour) with gelatin powder is combined to produce Kerapu’s fishballs which are high in fiber and low in cholesterol. The purpose of this study was to produce and improve the sensory quality of Kerapu’s fishtballs and improve the nutrition and functional aspects on health. The stages in Kerapu’s fishball production are consists of making surimi, determining the formulation of fishball, and analyzing the sensory quality. The results of the study are presented in the mean and standard deviation as well as statistical analysis performed to evaluate the quality of Kerapu’s fishball using ANOVA with Completely Randomized Design (CRD) and significant differences (p <0.05) and then continued with a significant difference test using the Duncan method. The test results for the level of acceptance of the grouper fish meatball product formulated in the treatment group showed the best level of acceptance in the P3 treatment (porang flour: gelatin = 50%: 50%) with the value of each hedonic test attribute as follows color, aroma, taste, aftertaste, texture and overall, namely 4.75, 4.80, 4.50, 4.65, 4.80, and 4.65 with an average acceptance of very like (5) with a level of elasticity of 3.30 ± 0.30 (slightly chewy). Therefore, the best formulation for producing grouper fish meatballs is grouper fish surimi (75%), porang flour: gelatin (2.5%:2.5%), 3% salt, pepper (2%), and water (15%). Keywords: Fishballs; Dietary Fiber, Kerapu; Sensory